Penggunaan Dana Infak Untuk Pembangunan Eco Masjid Perspektif Maqasid Syariah (Studi BAZNAS Kabupaten Jombang) - arivatu ni'mati rahmatika; iit Mazidah; Naily el-Muna (Jurnal Ilmiah Ekonomi Islam, 2021)
In the Islamic economic system, infaq is an instrument in the distribution of wealth as a form of gratitude for the pleasures that Allah has given to his people. Indonesia is a country that has abundant natural resources. Muslims are caliphs on earth who are given the authority to regulate everything that exists on earth. In relation, Eco Mosque is the development of places of worship that have concern for the reciprocal relationship between the environment for a sustainable life. Nature is managed and utilized for the common good and welfare. This type of research is a qualitative research with exploratory methods and content analysis using descriptive analysis as the nature of the research. The purpose of this study is to determine whether or not the use of infaq funds is allowed in the construction of the Eco Mosque program in the perspective of maqasid sharia. In this case, it is concluded that infaq funds in the perspective of Maqasid Sharia may be used in the construction of the Eco mosque, because it is intended for the welfare and benefit of the people.